2000
DOI: 10.1053/jpro.2000.20805
|View full text |Cite
|
Sign up to set email alerts
|

Periodic evaluation of the occlusal vertical dimension of maxillary dentures from the wax trial denture through 48 hours after polymerization

Abstract: Purpose: This study measured the effects of commercial resin type on maxillary complete dentures with monoplane teeth by periodically comparing the occlusal vertical dimension of the polymerized dentures with the baseline, wax trial denture fiducial measurements.Materials and Methods: Commercially available compression-molded, injection-molded, and fluid poly(methyl methacrylate) resins, as well as one compression-molded methyl acrylate ester copolymer, were evaluated. Ten dentures were fabricated from each re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…2,4,6-9 some have merely concerned a single jaw, 4,6 while others have considered both jaws. 2,[7][8][9]14,15 The present study has included completely edentulous patients master casts on which teeth were setup.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,4,6-9 some have merely concerned a single jaw, 4,6 while others have considered both jaws. 2,[7][8][9]14,15 The present study has included completely edentulous patients master casts on which teeth were setup.…”
Section: Discussionmentioning
confidence: 99%
“…Keenan et al 4 compared the occlusal and vertical height stability of complete removable dentures prepared by different combinations of injection/compression molding and microwave/hot air oven heating and found no significant differences between the groups after 28 days. Swards et al 6 reported that the OVDs of dentures prepared with compression molding and heat polymerization were significantly changed after processing. All groups showed significant differences in the vertical height after 48 hours, but the changes were smaller than with the remounting process.…”
Section: Jcdpmentioning
confidence: 99%
See 3 more Smart Citations